Comparing Some Biomechanical Variables of One Leg and Two Legs Jump Shot In Handball - Abbaas, Mahmoud; Khalil, Myshiq (Journal of Physical Education, 2019)
The research aimed at designing a test for jump shot accuracy for back court handball players as well as identifying the differences among results value. The researchers used the descriptive method. The subjects were (10) primer league handball clubs season (2018 – 2019). Six clubs were selected (Al Shorta – Al Kurk – Al Jaish – Al Mesaib – Al Selaymania – Al Fetowa) from which (39) backcourt players were selected to apply the main experiment. The data was collected and treated using proper statistical operations. The researchers concluded that jump shot with both legs is better and higher than one leg jump shot.